Pengaruh Burnout Terhadap Kinerja Karyawan pada Cibiuk Resto Lembang - Nurmaulidina, Bunga; Kusuma, Siska Fajar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of Burnout on employee performance at Cibiuk Resto Lembang. Burnout, which is a condition of physical and emotional exhaustion due to prolonged job stress, is believed to affect the quality of performance is believed to affect the quality of performance provided by employees. by employees. In this study, a quantitative approach approach was used with a survey method to collect data from employees who work at Cibiuk Resto Lembang. working at Cibiuk Resto Lembang. Data was obtained through a questionnaire filled out by 35 randomly selected employees. The Burnout variable was measured using the Maslach Burnout Inventory (MBI) scale, while performance quality was measured using a questionnaire consisting of indicators such as the was measured using a questionnaire consisting of indicators such as speed, friendliness, and accuracy of performance. The results of this study are based on calculation of simple linear regression analysis, it is known that the Burnout variable has no significant effect on employee performance. variable has no significant effect on employee performance. This is indicated by the significance value in the t test (0.700> 0.05), as well as the very small R square value (0.005). square value which is very small (0.005). This means that the Burnout variable only explains 0.5% of the variation in employee performance, while the rest is explained by other factors outside the model. explained by other factors outside the model.